The Resurgence of Ideology in Indonesia: Political Islam, Aliran and Political Behaviour. Issue 2 (August 2019) - Fossati, Diego
The 2019 Indonesian presidential elections indicate that ideology played an important role in voting behaviour, as aggregate subnational results seem to mirror the mid-1950s, when Indonesian politics was organised around ideological and partisan groups known as aliran . However, the extent to which these macro-level patterns are rooted in real ideological divisions among Indonesian voters is an open question. This article analyses an original survey specifically designed to measure aliran identities, ideological orientations and political preferences of ordinary Indonesians. Findings indicate that aliran identities are still present and associated with party choice but only loosely connected with political ideology. Most notably, however, political Islam is associated with important political attitudes and behaviours. Islamist Indonesians are less likely to support liberal understandings of democracy, more likely to see economic issues as policy priorities and more likely to support economic redistribution and regional autonomy. This suggests that ideology should receive greater attention in the study of Indonesian politics.